Cover Page Information - Carvajal Garavito, Jessica Silena (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The cover artist, Jessica Silena Carvajal Garavito, from the Universidad Pedagógica y Tecnológica de Colombia and Community College of Philadelphia, reflects on her inspiration and choices for the cover.